Pengaruh Pemberian Filler Abu Cangkang Lokan Terhadap Parameter Marshall Pada Campuran Aspal Beton - Veranita Veranita; Chaira Chaira (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2019)
West Aceh has a coastline area and a river that drains water into the sea which is quite extensive and produces a lot of supply of lokan species that live in the river. Lokan is a special food that is served by many noodle stalls and restaurants in the area, while the shells become waste that has not been fully utilized. The availability of these shells originating from household waste has inspired the author to conduct research on the use of these as fillers. The shell fillers have little in common with cement fillers are equally lime-containing which can improve the carrying capacity of a mixture. The price is also cheaper and friendly to the environment. From this study the authors wanted to find out the effect of graft ash filler on Marshall parameters on concrete asphalt mixture. The research carried out refers to the technical specifications of the Department  of  Public  Works  2010.  Variations  in  the  filler  mixture  used  have  different compositions. The percentage of filler used for each variation is the addition of 0% cement filler and 100% shell ash, 20% cement ash filler addition and 80% shell ash, and 50% cement ash filler addition and 50% shell shell ash. The results obtained for optimum bitumen content in variations  of  0/100, 20/80  and  50/50  were  4.8%, 4.5%,  and  4.9%  respectively.  From  the Marshall evaluation results obtained the highest stability values at variations of 0/100, and the lowest in the variation of 50/50, this shows that the higher the content of shell shell ash will increase the higher carrying value but less flexible.